PENGARUH CURRENT RATIO (CR), DEBT TO EQUITY RATIO (DER), EARNING PER SHARE(EPS), RETURN ON EQUITY (ROE), DAN PRICE EARNING SHARE (PER) TERHADAP RETURN SAHAM PADA PERUSAHAAN FOOD AND BEVERAGE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Layla Hafni; Vivi Anggraini S (Bilancia : Jurnal Ilmiah Akuntansi, 2018)
This research was conducted to test the influence of Current Ratio (CR), Debt to Equity Ratio (DER), Earning Per Share (EPS), Return On Equity (ROE), and Price Earning Ratio (PER) to Return of Stock at Food and Beverage Company listed on the Indonesia Stock Exchange. Before performing the hypothesis test, a few classical assumption tests are performed, including the Data Normality Test, Multicolinearity Test, Autocorrelation Test, Heteroscedasticity Test. In the analysis results determine that the variable Current Ratio (CR), Debt to Equity Ratio (DER), Earning Per Share (EPS), and Return On Equity (ROE), partially no effect on Stock Return, while Price Earning Ratio (PER) significant effect on Stock Return. The prediction ability of the five variables to the Return of Stock is 10.2% indicated by the adjusted R square, while the remaining 89.8% is influenced by other variables which are not examined. Penelitian ini dilakukan untuk menguji pengaruh Current Ratio (CR), Debt to Equity Ratio (DER), Earning Per Share (EPS), Return On Equity (ROE), dan Price Earning Ratio (PER) terhadap Return Saham pada perusahaan Food and Beverage yang terdaftar di Bursa Efek Indonesia.Sebelum melakukan uji hipotesis, dilakukan terlebih dahulu beberapa uji asumsi klasik yang meliputi Uji Normalitas Data, Uji Multikolinearitas, Uji Autokorelasi, Uji Heteroskedastisitas. Dalam hasil analisis menentukan bahwa variabel Current Ratio (CR), Debt to Equity Ratio (DER), Earning Per Share (EPS), dan Return On Equity (ROE), secara parsial tidak berpengaruh terhadap Return Saham, sedangkan Price Earning Ratio (PER) berpengaruh signifikan terhadap Return Saham. Kemampuan prediksi dari kelima variabel tersebut terhadap Return Saham sebesar 10,2% ditunjukkan oleh besarnya adjusted R square, sedangkan sisanya 89,8% dipengaruhi oleh variabel lain yang tidak diteliti.